2012
DOI: 10.1016/j.neulet.2011.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered l-ornithine reduces restraint stress-induced activation of the hypothalamic-pituitary-adrenal axis in mice

Abstract: In a previous study, we confirmed that orally administered L-ornithine can be transported into the brain of mice. In addition, orally administered L-ornithine, within a limited dose range, had an anxiolytic-like effect in the elevated plus-maze test. However, the mechanism by which orally administered L-ornithine reduced the stress response in mice is still unclear. Experiment 1 determined whether orally administered L-ornithine could reduce the stress-induced activation of hypothalamic-pituitary-adrenal axis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Similarly, in experimental animals, chronic stress paradigms can recapitulate not only many behavioural characteristics but also a number of biochemical states of depression, including corticosterone and ACTH levels and neurochemical changes [1]. The results of this study showed that CUS caused significant reductions in the levels of 5-HT, NA, 5-HIAA and DA in rat brain, increases in the 5-HIAA/5-HT ratio in rat brain as well as increases in the levels of corticosterone and ACTH in rat serum, which are consistent with other studies [2][3][4][5]12]. The present study also showed that paeoniflorin treatment not only significantly increased the concentrations of NA, 5-HIAA and 5-HT and decreased the 5-HIAA/5-HT ratio in the CUS-induced rat brain but also decreased the serum corticosterone and ACTH levels.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in experimental animals, chronic stress paradigms can recapitulate not only many behavioural characteristics but also a number of biochemical states of depression, including corticosterone and ACTH levels and neurochemical changes [1]. The results of this study showed that CUS caused significant reductions in the levels of 5-HT, NA, 5-HIAA and DA in rat brain, increases in the 5-HIAA/5-HT ratio in rat brain as well as increases in the levels of corticosterone and ACTH in rat serum, which are consistent with other studies [2][3][4][5]12]. The present study also showed that paeoniflorin treatment not only significantly increased the concentrations of NA, 5-HIAA and 5-HT and decreased the 5-HIAA/5-HT ratio in the CUS-induced rat brain but also decreased the serum corticosterone and ACTH levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, micro infusion of GABA agonists, such as the stress-derived neurosteroid tetrahydrodeoxycorticosterone (THDOC), into the paraventricular nucleus (PVN) decreased circulating levels of stress hormones [35]. Our result showing that orally administered L-ornithine decreased the serum cortisol level in human subjects was in agreement with previous animal studies on the effectiveness of stress reduction through the alleviation of HPA axis hyperactivity [20,31-34]. …”
Section: Discussionsupporting
confidence: 90%
“…That action was mediated by GABA A receptors. It was also confirmed that orally administered L-ornithine can be transported into the brain of mice [20], and as a result, reduced the plasma corticosterone concentration induced by restraint stress in mice. L-ornithine levels in the brain increased after oral administration of L-ornithine in mice [20].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations